A "autoficção" narrativa: impasses e ambiguidades literários. A propósito de Chove sobre minha infância, de Miguel Sanches Neto - Freire, Vanessa Maidana (2010)
In this work we propose basically a theoretical-critical review and an approach to analyze the autofiction genre Chove sobre minha infância, 2000 by Miguel Sanches Neto, focusing on the existence and function of non-verbal elements incorporated in the literary discourse. This narrative text is composed by two different literary genres: the romance (novel) and the autobiography. These discursive registers come together to suggest a new genre in the literature, becoming a new object of study in our field. Due to the discursive heterogeneity, the narrative presents some situation and theoretical problems which, firstly, we aim to explain it by presenting the literature review and debates about autobiographies and autofiction genres. Secondly, we are going to highlight the function of non-verbal analysis as a setting contribution to the verbal discourse, as well as the problems resulting from the integration of non-verbal signs into the fictional text.